Peran Komunikasi Politik Dalam Membentuk Opini Publik Menghadapi Pemilu 2024 - Nuraliza, Vadhea; Andhi Nur Rahmadi; Alvan Mubaroq; Kristiyono Kristiyono; Alisyia Putri Melani; Anila Ifana (Lembaga Pengembangan Kinerja Dosen, 2024)
The 2024 General Election (Pemilu) is a crucial stage in the dynamics of democracy, where the role of political communication plays a central role in shaping public opinion. This phenomenon creates a need to understand in depth the influence of political communication on public perceptions of candidates, political parties, and crucial issues that influence the direction of state policy. This research aims to analyze the role of political communication in shaping public opinion ahead of the 2024 elections. The main focus is understanding how political communication strategies, including message personalization, social media, and investigative journalism, influence the formation of public opinion and voter participation. The research method used is descriptive qualitative. Data was collected through literature reviews, media content analysis, and interviews with political communication experts. A qualitative approach is used to deepen understanding of the complexity of political communication strategies and their impact on public opinion. The research results show that political communication strategies, especially message personalization, have a significant impact in shaping public opinion. Candidates who are able to connect emotionally with voters through personal life stories and values ​​build strong identification. Social media plays an important role in expanding the reach of political messages, while investigative journalism makes a major contribution in uncovering basic facts and maintaining the integrity of information.